Peran Pendidikan Kewarganegaraan terhadap Partisipasi Politik Remaja - Ramadhan, Defry Eza; Saputra, Alvan Dwi; Hamid, Syukri Al Hamid (PT Elaborium Elevasi Indonesia, 2024)
This research has a background in the low political participation of teenagers. As a democratic country, Indonesia needs people who are aware of the importance of political participation. Teenagers are a benchmark that determines the future. As someone who is still unfamiliar with politics, teenagers still need more guidance and knowledge to be able to participate in the world of politics. This research uses a literature review method by taking data from various sources such as journals, articles and official publications related to citizenship education and also youth political participation. The aim of this research is to find out that good citizenship education can increase teenagers' political awareness and enable them to be more active in the political process, thereby improving the quality of democracy in a country.